The technology mismatch paradox of mobile e-mail access: When changed norms of responsiveness meet technology undersupply. Issue 3 (27th May 2017) - Loeschner, Isabell
ABSTRACT: Connectivity, enabled by mobile devices and mobile e-mail access in particular, plays an increasingly important role at work. While there is a growing body of literature on employees who experience great levels of connectivity, little is known about those who have low levels of connectivity because they have not been provided with mobile devices for work. When highly connected individuals collaborate with less technologically equipped employees, the latter have to negotiate their work practices in a demanding space of expectations and technological constraints and affordances. This article examines these dynamics via mixed-methods case studies of two public-sector organizations in Germany.